Desarrollo rural: parques agroindustriales - Palacios Lozada, Enrique E. (2013)
Several rural development models have been implemented with a conceptual basis of modernity; increased production and agricultural productivity, factors required but not sufficient to sustain the operation of rural society and its development. The proposed model is based on the implementation of agroindustry parks which allow: technological development, higher added value, employment generation and management development. Its importance and applicability provide a solution to structural issues and conjuncture of the rural world.